2007
DOI: 10.1128/jcm.00374-07
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between Infections with Different Genotypes of Human Cytomegalovirus and Epstein-Barr Virus in Subgingival Samples and Periodontal Status of Patients

Abstract: Accumulating evidence indicates that herpesviruses may be putative pathogens in various types of periodontal diseases. The present study was performed to examine infections with different genotypes of human cytomegalovirus (HCMV) and Epstein-Barr virus (EBV) in subgingival samples from a Chinese population and to analyze the correlation with periodontal status. A nested PCR assay was used to identify the presence of HCMV, EBV type 1 (EBV-1), and EBV-2; and the amplicons were further analyzed by restriction fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 37 publications
5
65
1
3
Order By: Relevance
“…Only 2 of 4 HCMV gB genotypes were detected in periapical lesions, gB-I and gB-II. Our results are in accordance with previously reported occurrence of HCMV gB genotypes in generalized chronic periodontitis and periimplantitis tissues (25,26). Similarly, these studies reported the absence of HCMV gB-III and gB-IV in their samples.…”
Section: Clinical Researchsupporting
confidence: 96%
See 1 more Smart Citation
“…Only 2 of 4 HCMV gB genotypes were detected in periapical lesions, gB-I and gB-II. Our results are in accordance with previously reported occurrence of HCMV gB genotypes in generalized chronic periodontitis and periimplantitis tissues (25,26). Similarly, these studies reported the absence of HCMV gB-III and gB-IV in their samples.…”
Section: Clinical Researchsupporting
confidence: 96%
“…Our results also corroborate some previous findings regarding EBV genotypes in oral pathologies. Wu et al (25) reported the presence of both EBV genotypes in tissue samples of generalized chronic periodontitis, with significantly higher frequencies of EBV-1, whereas Jankovic et al (26) found that EBV-1 was more frequent in samples of periimplantitis and mucositis compared with EBV-2. The occurrence of EBV-2 has been mostly found in immunocompromised patients such as HIV-infected and transplant recipients (24).…”
Section: Clinical Researchmentioning
confidence: 97%
“…To obtain more precise information about the role of herpesviruses in the etiopathogenesis of peri-implantitis and periodontitis the highlights from the study by WU et al 30 must not be avoided. These findings clearly indicate that HCMV gB-II and EBV-1 are the dominant virus genotypes detected in subgingival samples in aggressive and chronic periodontitis.…”
Section: Discussionmentioning
confidence: 98%
“…The overall detection rate for HCMV DNA when nested PCR was used at individual sites with periodontitis was similar to the prevelance of CMV in peri-implantitis sites 65% (62% 14 , 64% 4 , 59% 26 , 63% 30 ). EBV DNA was detected in the subgingival plaque of periodontaly diseased sites in approximately 30% and in 8% of healthy sites 11,19,27,30 . In this study the presence of EBV DNA in peri-implantitis sites was higher at 45%.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of studies found some possible association between gB genotype and infection course (Fries et al, 1994; Shepp et al, 1996; Rasmussen et al, 1997; Meyer-König et al, 1998; Cunha Ade et al, 2002; Wu et al, 2007; Roubalová et al, 2010; Madi et al, 2011; Xia et al, 2012; Vogel et al, 2013), other studies did not found any correlation (Lurain et al, 1999; Trincado et al, 2000; Sarcinella et al, 2002; Carraro and Granato, 2003; Tarragó et al, 2003; Tanaka et al, 2005; Yamamoto et al, 2007; Görzer et al, 2010; Wu et al, 2011; Paradowska et al, 2012). Some reports also indicated that infection with mixed genotypes could be related to disease progression (Sarcinella et al, 2002; Coaquette et al, 2004; Pang et al, 2008; Deckers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%